DETERMINAN KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH: STUDI PADA OPD PEMERINTAH KOTA PEKANBARU - Justika Zebua; Muhammad Rasuli; Vera Oktari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Riau, 2020)
This study aims to explain how Human Resources Competencies, Utilization of Information Technology and The Application of Internal Control System determine of the Quality of Financial Reports of Pekanbaru City. This study uses a quantitative method. The population in this study were 33 OPD in Pekanbaru City Government. The sample determination technique uses a purposive sampling method, where questionnaires distributed to 99 respondents were determined to the Head of Department, Head of Division/Sub-Division/Financial Staff and PPTK of each OPD. The hypothesis test used in this study uses t-Test. The statistical test aids used in this study were the SPSS program ver. 20 for Windows and Ms. Excel 2013. The results show that the Competencies of Human Resources, Utilization of Information Technology and the Application of Internal Control System partially affected the Quality of Local Government Financial Reports